Environmental Impact Analysis on Furniture Industry by Implementing Life Cycle Assessment (LCA) Method - Aulia Dita Ananda Lestari; Farida Pulansari (Advance Sustainable Science Engineering and Technology, 2025)
Currently the industry is experiencing an increase every year. One of them is the furniture production industry. In East Java there is a furniture industry which experiences an increase in production demand every year. This does not only apply to local consumers but also foreign consumers. PT XYZ implements a make to order system, namely products are made when consumers order them. The amount of production demand is directly proportional to the amount of industrial waste produced, but the company has never carried out an analysis of the impacts. Therefore, this research will discuss environmental impact analysis using life cycle assessment to calculate the life cycle value of the production of a furniture product with cradle to gate limitations. This research was assisted by OpenLCA 2.1.0 software using the Agribalyse_301 database and then for impact assessment using the EDIP 2003 method. After calculating, recommendations for improvement were looked for to reduce the resulting environmental impact. The results of this research for 1 unit of table product production are 3.51166 Pt. The highest impact was produced by the production process, namely Ozone depletion of 0.58215 Pt. This impact can pollute the environment due to the large use of electricity. It is best for companies to use electricity from renewable sources.